Using statistical population reconstruction to estimate the effect of pelt prices on river otter abundance and harvest vulnerability in Kentucky - Berg, Sergey S.; Palmer, Laura L. (Frontiers in Mammal Science, 2025)
IntroductionAccurately estimating the abundance, survival rates, and harvest vulnerability of harvested populations of North American river otters (Lontra canadensis) is essential for their effective management and conservation. Monitoring these rates over time allows for more informed decision-making regarding harvest regulations such as quotas, bag limits, and season lengths, and can also be used to evaluate the impact of various anthropogenic stressors such as rising pelt prices and increased trapper effort.MethodologyWe used age-at-harvest, catch-effort, and radio-telemetry data to parameterize a second-stage statistical population reconstruction model with both fixed and linear effects to estimate abundance and harvest vulnerability of river otter in Kentucky, USA from 2012 to 2023. We then used this model to investigate the effect that interannual fluctuations in pelt prices during this time likely had on the population in terms of both harvest mortality and overall abundance.ResultsOur results suggest that the measurable decline in overall abundance from 2012 to 2016 was caused by higher pelt prices from 2012 to 2014, which resulted in above-average harvest intensity during those three years. Our results also suggest that although higher pelt prices resulted in more catch-effort, they may have counterintuitively decreased the likelihood of a river otter being harvested per additional unit of catch-effort, possible attributable to more casual or inexperienced trappers shifting their focus to river otters to maximize profits.DiscussionOur findings illustrate the utility of using statistical population reconstruction with linear effects to help management agencies better understand the likely driving forces behind observed interannual fluctuations in abundance, survival, and harvest vulnerability of river otters and other furbearer species that are in high demand by the public.